Optimizing Healthy Pregnancy Through Prenatal Yoga: An Effectiveness Study on Primigravida at Independent Midwifery Practices in East Lampung - Pratiwi, Fisca; Wulandari, Ririn; Sari, Desi Kumala (Women, Midwives and Midwifery, 2025)
Background: One intervention that can be undertaken by pregnant women to support optimal pregnancy outcomes is prenatal yoga. Yoga is a discipline that integrates physical, mental, and spiritual practices aimed at achieving holistic health, which can be incorporated into daily life. The purpose of this study was to examine the effectiveness of prenatal yoga on pregnancy outcomes among primigravida women at Independent Midwifery Practices in Batang Hari, East Lampung, in 2025. Methods: This study employed a quantitative research approach, using a quasi-experimental design with a post-test only control group. The study population included third-trimester primigravida women, and data collection was conducted at the independent midwifery practices of Bd. Amelia Agustina, S.Keb., and Bdn. Sri Umi, S.ST., between January and March 2025. The Mann-Whitney test was used for data analysis. Result: The findings revealed that the average post-test score for maternal outcomes in the prenatal yoga intervention group was 0.40, while the average post-test score for perinatal outcomes in the same group was 0.27. In the control group, the average post-test score for maternal outcomes was 1.80 with a standard deviation of 0.775, and the average score for perinatal outcomes was 0.93. A statistically significant difference was observed between the intervention and control groups, with a p-value of 0.000. Conclusion: These results indicate that prenatal yoga is effective in improving pregnancy outcomes among primigravida women at the Independent Midwifery Practices in Batang Hari, East Lampung, in 2025.